IECON 2018 - 44th Annual Conference of the IEEE Industrial Electronics Society 2018
DOI: 10.1109/iecon.2018.8591451
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight and Low-Energy Encryption Scheme for Voice over Wireless Devices

Abstract: In this work, a novel lightweight and low energy encryption algorithm for voice over wireless networks is being developed and tested. The new encryption algorithm has to meet the QoS requirements of voice traffic and to be suitable for wireless devices. The goal of the research was to reduce the execution time and power consumption of the encryption process compared with the standard algorithm and at the same time at least to maintain or to increase its security level. The proposed algorithm employs similar me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Some of them focus on developing algorithms that suit dealing with real time limitations such as delays while some others focus on the complexity of the security algorithm and neglect the performance (encryption delay, Energy) requirements. This work expands our previous work [20] which developed a new lightweight encryption scheme. The main contribution of this paper is to conduct further security analyses which are missing in previous works and to test brute force attack on the newly proposed algorithm.…”
Section: Literature Reviewsupporting
confidence: 62%
“…Some of them focus on developing algorithms that suit dealing with real time limitations such as delays while some others focus on the complexity of the security algorithm and neglect the performance (encryption delay, Energy) requirements. This work expands our previous work [20] which developed a new lightweight encryption scheme. The main contribution of this paper is to conduct further security analyses which are missing in previous works and to test brute force attack on the newly proposed algorithm.…”
Section: Literature Reviewsupporting
confidence: 62%
“…When it comes to encryption time, the suggested encryption method has outperformed AES. A low-power as well as lightweight encryption technique is suggested by the authors in [7] for safeguarding voice communication over wireless networks. The suggested algorithm works well with wireless devices and satisfies voice traffic requirements.…”
Section: Related Studymentioning
confidence: 99%
“…Reported results in [16] have shown that the enhanced KP-ABE model remarkably offers low running time as compared to other similar encryption algorithms. In [17], an enhanced version of the AES encryption algorithm in terms of running time and energy consumption has been presented. Obtained results in [17] have confirmed it is fair to claim that enhanced algorithm is lightweight and efficient for voice applications in wireless systems.…”
Section: Tth Wireless Communication Link In General Is Insecure and Omentioning
confidence: 99%
“…In [17], an enhanced version of the AES encryption algorithm in terms of running time and energy consumption has been presented. Obtained results in [17] have confirmed it is fair to claim that enhanced algorithm is lightweight and efficient for voice applications in wireless systems. In [18], a hybrid lightweight encryption algorithm for IoT networks has been proposed.…”
Section: Tth Wireless Communication Link In General Is Insecure and Omentioning
confidence: 99%